Strategi Kompetisi Meraih Kemenangan Lembaga Pendidikan Islam di Era Digital (Studi Kasus di MAN 1 Kota Kediri) - Sahid, Nur; Nafidatus S , Dyah (Tim Jurnal STAI KH. Zainuddin Ponpes Mojosari, 2025)
Islamic education in the national education system must comprehensively and continuously evaluate the opportunities and challenges of the digital era to strengthen its role in forming a better generation mentally, spiritually, morally, socially and creatively. The importance of Islamic education strategies in the digital era to achieve victory and compete in intense global competition. MAN 1 Kediri City is an example that has implemented digitalization both in the learning process and administrative fields to prepare a generation of qualified Muslims. The method used in this research is a qualitative method by collecting data through observation and interviews with descriptive analysis techniques. The results of the research show that MAN 1 Kediri City has succeeded in implementing strategies to achieve victory in the digital era through the use of digital technology in learning, implementation of vocational programs, competency-based curriculum development, character and moral education, and the use of social and digital media.